Revision of carpenter bees of the subgenus Neoxylocopa Michener (Hymenoptera: Apidae) from Mexico and Mesoamerica - Mérida-Rivas, Jorge A.; Hinojosa-Díaz, Ismael A.; Ayala-Barajas, Ricardo; Barrientos-Villalobos, S.; Pozo, Carmen; Vandame, Rémy (Zootaxa, 2022)
We present a review of the genus Xylocopa (Neoxylocopa) of Mexico and Mesoamerica in which 11 species are recognized, including: X. clarionenis, X. fimbriata, X. frontalis, X. gualanensis, X. mexicanorum, X. nautlana, X. ocellaris, X. sonorina, X. wilmattae. Additionally, two new species are described, X. griswoldi sp. nov. with distribution in the United States and Mexico, and X. maya sp. nov. present in Mexico and Belize. Three species groups within the subgenus Neoxylocopa are recognized: frontalis, mexicanorum and sonorina. Identification keys are presented for identifying species groups and species. Furthermore, images of species and morphological structures as well as information regarding distribution are provided.